UHRF1 regulation of the Keap1–Nrf2 pathway in pancreatic cancer contributes to oncogenesis. Issue 3 (30th November 2015) - Abu‐Alainin, Wafa; Gana, Thompson; Liloglou, Triantafillos; Olayanju, Adedamola; Barrera, Lawrence N; Ferguson, Robert; Campbell, Fiona; Andrews, Timothy; Goldring, Christopher; Kitteringham, Neil; Park, Brian K; Nedjadi, Taoufik; et al.
Abstract: The cellular defence protein Nrf2 is a mediator of oncogenesis in pancreatic ductal adenocarcinoma (PDAC) and other cancers. However, the control of Nrf2 expression and activity in cancer is not fully understood. We previously reported the absence of Keap1, a pivotal regulator of Nrf2, in ∼70% of PDAC cases. Here we describe a novel mechanism whereby the epigenetic regulator UHRF1 suppresses Keap1 protein levels. UHRF1 expression was observed in 20% (5 of 25) of benign pancreatic ducts compared to 86% (114 of 132) of pancreatic tumours, and an inverse relationship between UHRF1 and Keap1 levels in PDAC tumours ( n = 124) was apparent ( p = 0.002). We also provide evidence that UHRF1‐mediated regulation of the Nrf2 pathway contributes to the aggressive behaviour of PDAC. Depletion of UHRF1 from PDAC cells decreased growth and enhanced apoptosis and cell cycle arrest. UHRF1 depletion also led to reduced levels of Nrf2‐regulated downstream proteins and was accompanied by heightened oxidative stress, in the form of lower glutathione levels and increased reactive oxygen species. Concomitant depletion of Keap1 and UHRF1 restored Nrf2 levels and reversed cell cycle arrest and the increase in reactive oxygen species. Mechanistically, depletion of UHRF1 reduced global and tumour suppressor promoter methylation in pancreatic cancer cell lines, and KEAP1 gene promoter methylation was reduced in one of three cell lines examined. Thus, methylation of the KEAP1 gene promoter may contribute to the suppression of Keap1 protein levels by UHRF1, although our data suggest that additional mechanisms need to be explored. Finally, we demonstrate that K‐Ras drives UHRF1 expression, establishing a novel link between this oncogene and Nrf2‐mediated cellular protection. Since UHRF1 over‐expression occurs in other cancers, its ability to regulate the Keap1–Nrf2 pathway may be critically important to the malignant behaviour of these cancers. © 2015 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.